Cyanobacterial Toxins of Drinking Water Supplies - Falconer, Ian Robert (CRC Press, 2009)
The contamination of both drinking and recreational water supplies by cyanobacteria is increasingly a cause for concern worldwide. While contamination causes livestock deaths with relative frequency, acute poisoning is rare in humans. However, there is growing apprehension over the possible role of cylindrospermopsins and microcystins in gastrointestinal and liver cancer.